Penerapan Pendekatan Pembelajaran Koperatif Tipe Make A Macth Untuk Meningkatkan Prestasi Belajar Siswa Mata Pelajaran IPS Kelas II SDI Elhakim Bagik Lonjer Tahun Pelajaran 2019/2020 - Indriani, Husna (FAKULTAS TARBIYAH, 2020)
This research is motivated by the conditions faced in the social studies learning process, which is caused by the way teachers teach who still use monotonous methods and when learning takes place students to seem less interested in the learning delivered by educators. The focus of the problem is how to improve student learning outcomes by applying the Make a Match type of cooperative learning model in the Social Sciences subject for sale and purchase material in the II SDI class, Elhakim Bagik Lonjer, Kec. Sakra Barat 2020/2021 academic year. The aim is to describe the application of the make-a-match type of cooperative learning model and social studies learning outcomes in the buying and selling materials for the IISDI class, Elhakim Bagik Lonjer, Kec. Sakra Barat 2020/2021 Academic Year. This study uses two cycles of Classroom Action Research. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The objects of this research are II SDI class students, Elhakim Bagik Lonjer, and Kec. Western Sakra. Techniques used in collecting data include tests, observations, and documentation. The data analysis used includes data reduction, data presentation, and drawing conclusions. The success indicator in this study is if the mastery of the students' material reaches 75% of the goals that should be achieved, with a KKM score of 70. The results showed that social studies learning using the Make A Match type could improve student learning outcomes in buying and selling materials. This is indicated by the learning outcomes of students. In the first cycle, the average score of students was 71.76 with students' classical learning completeness of 64% and the average score of student activity was 11.61 with a fairly active category. In the second cycle with an average score of 77.29 with students' classical learning completeness of 88% and the average score of student learning activities reaching 14.76 in the active category. Based on the results of the study, it can be concluded that the use of a make-a-match type of cooperative learning approach can improve the social studies learning achievement of Class II students of SDI Elhakim Bagik Lonjer.